The effect of DNA recovery on the subsequent quality of latent fingermarks: A pseudo-operational trial. (February 2020) - Fieldhouse, S.; Parsons, R.; Bleay, S.; Walton-Williams, L.
Highlights: A pseudo-operational trial of gel DNA recovery on latent fingermark quality. User variation effects on fingermarks were examined. Fingermarks deemed 'suitable for identification' were observed post gel lifting. Surface type was a greater influence on fingermark quality than DNA recovery. Low weight and instantaneous gel application was least detrimental to marks. Abstract: The recovery of fingermarks and DNA from the same location at a crime scene can be problematic because of contamination issues associated with powdering or laboratory-based visualisation processes and/or the perceived destructive impact of commonly employed 'swabbing' approaches to DNA recovery. Previous research in a controlled environment demonstrated that it was possible to recover DNA and latent fingermarks from the same location on various substrates when an adhesive approach to DNA recovery was used. The aim of this research was to conduct a pseudo-operational trial into the dual recovery of DNA and fingermarks using gel lifters for DNA recovery. Participants were asked to voluntarily and anonymously donate a wide variety of porous and non-porous substrates post handling. No instruction as to fingermark deposition nor environmental storage was provided. BVDA gel lifters were applied to the substrates to replicate DNA recovery followed by the application of fingermark visualisation processes. The number and quality of the fingermarks was established using a grading approach. Application factors were also investigated to consider the effects of user variation. The results demonstrated that it was possible to recover DNA and fingermarks considered to be capable of supporting an identification. Fingermark quality post lifting was dependant on the substrates used. The weight applied to the gel during its application was a lesser contributing factor than the duration of its contact with the surface. There was a greater chance of leaving the fingermarks unaltered with the application of a low weight and instantaneous retraction.